Association between overall diet quality and postmenopausal breast cancer risk in five Finnish cohort studies - Satu Männistö (Nature Portfolio, 2021)
Abstract There is limited evidence for any dietary factor, except alcohol, in breast cancer (BC) risk. Therefore, studies on a whole diet, using diet quality indices, can broaden our insight. We examined associations of the Nordic Diet (mNDI), Mediterranean diet (mMEDI) and Alternative Healthy Eating Index (mAHEI) with postmenopausal BC risk. Five Finnish cohorts were combined including 6374 postmenopausal women with dietary information. In all, 8–9 dietary components were aggregated in each index, higher total score indicating higher adherence to a healthy diet. Cox proportional hazards regression was used to estimate the combined hazard ratio (HR) and 95% confidence interval (CI) for BC risk. During an average 10-year follow-up period, 274 incident postmenopausal BC cases were diagnosed. In multivariable models, the HR for highest vs. lowest quintile of index was 0.67 (95 %CI 0.48–1.01) for mNDI, 0.88 (0.59–1.30) for mMEDI and 0.89 (0.60–1.32) for mAHEI. In this combined dataset, a borderline preventive finding of high adherence to mNDI on postmenopausal BC risk was found. Of the indices, mNDI was more based on the local food culture than the others. Although a healthy diet has beneficially been related to several chronic diseases, the link with the etiology of postmenopausal BC does not seem to be that obvious.